2016
DOI: 10.1038/srep36062
|View full text |Cite
|
Sign up to set email alerts
|

Sebum and Hydration Levels in Specific Regions of Human Face Significantly Predict the Nature and Diversity of Facial Skin Microbiome

Abstract: The skin microbiome varies across individuals. The causes of these variations are inadequately understood. We tested the hypothesis that inter-individual variation in facial skin microbiome can be significantly explained by variation in sebum and hydration levels in specific facial regions of humans. We measured sebum and hydration from forehead and cheek regions of healthy female volunteers (n = 30). Metagenomic DNA from skin swabs were sequenced for V3-V5 regions of 16S rRNA gene. Altogether, 34 phyla were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(129 citation statements)
references
References 40 publications
(70 reference statements)
7
116
1
5
Order By: Relevance
“…For example, sebum secreted from the sebaceous glands appears to be an important determinant of the preferential colonization of Propionibacterium spp. (Mukherjee et al, 2016). …”
Section: Landscape Ecology Of the Human Nasal Cavitymentioning
confidence: 99%
“…For example, sebum secreted from the sebaceous glands appears to be an important determinant of the preferential colonization of Propionibacterium spp. (Mukherjee et al, 2016). …”
Section: Landscape Ecology Of the Human Nasal Cavitymentioning
confidence: 99%
“…5,6 Previous investigations demonstrated that the skin microbial community exhibits remarkable differences on topographically distinct areas depending on characteristics such as sebaceous gland concentration, moisture content, temperature, as well as host genetics and environmental factors. 7,8 Besides the diversity of microbiota, some researchers indicated a mutual relationship between the host and these microorganisms, because they play an important role in tissue homeostasis and local immunity. 9 Rosacea-affected skin shows altered fatty acids composition, 10 and it may result in imbalanced homeostasis of the skin microbiome.…”
Section: Sebaceous Glands Participate In the Inflammation Of Rosaceamentioning
confidence: 99%
“…The most commonly found viral families on adult skin include Cirocoviridae, Polyomaviridae, and Papillomaviridae . Body‐site specificity and stability are likely driven by innate skin characteristics including moisture, lipid content, pH, salinity, temperature, and environmental exposures including skin care products …”
Section: Healthy Children Microbiome Vs Healthy Adult Microbiomementioning
confidence: 99%
“…Pubarche has a profound effect on skin microbiome composition. Sex hormones trigger increased sebaceous gland and apocrine gland activity, resulting in increased skin lipids which favor the colonization and growth of lipophilic bacteria, including Cutibacterium acnes , at the expense of other skin commensals . Skin microbiota composition is also influenced by the host immune system, which is continuously adapting and likely contributes to the establishment of a stable, body‐site specific skin microbiome in adulthood.…”
Section: Healthy Children Microbiome Vs Healthy Adult Microbiomementioning
confidence: 99%
See 1 more Smart Citation